Evaluation of Female Pelvic Pain - Chandler, Jessica; Wagner, Elena; Riley, Kristin (Seminars in Reproductive Medicine, 2018)
Chronic pelvic pain is a condition defined by pelvic pain for more than six months which is severe enough to cause functional disability or require treatment. When pain becomes a chronic condition, it is more challenging to evaluate and treat. Chronic pelvic pain patients often have multiple factors contributing to their pain. Here, we review the approach to the evaluation of chronic female pelvic pain. It is important to establish a trusting patient–physician relationship. When evaluating a female patient with chronic pelvic pain, an in-depth history and targeted physical exam can localize contributors to pain. While limited, corresponding imaging and laboratory work should also be considered.
Keywords: chronic pelvic pain; physical exam; imaging